Guidance To Build Mental Well-Being: The Role Of Guidance And Counseling - Dwi Syamsih (Journal of Therapia, 2024)
Guidance and counseling plays a crucial role in helping individuals overcome various psychological and emotional problems in contemporary society. The need for these services is increasingly urgent, not only as a response to psychological crises, but also as an effort to prevent and build sustainable mental well-being. Research shows that guidance and counseling is effective in helping individuals overcome stress, anxiety, depression, as well as develop adaptive and problem-solving skills necessary in facing life's challenges. Moreover, the importance of this service lies not only in its individual dimension, but also in its contribution to overall public health. Through holistic and coordinated services, guidance and counseling can help reduce the burden of mental illness, increase productivity, and strengthen social and support networks. However, guidance and counseling practitioners are faced with new challenges and rapidly evolving opportunities, such as the application of technology in online counseling practices. In addition, social and cultural contexts play an important role in guidance and counseling practice, making the integration of cross-cultural perspectives an urgent necessity. In response to the evolving challenges and opportunities, guidance and counseling practitioners need to strengthen their competencies through continuous education, training, and professional development. New research and innovations in the fields of neuroscience, positive psychology, and technology-based therapies also have a significant impact on guidance and counseling, so practitioners must continue to adapt to the latest scientific developments. In an era where stress and life pressure are on the rise, a proactive approach in promoting mental wellbeing is becoming increasingly urgent. Therefore, guidance and counseling should not only focus on addressing problems, but also on prevention and building adaptive skills that can improve the overall quality of life. All in all, it can be concluded that guidance and counseling has a very important role in supporting the mental and social well-being of individuals as well as society at large.